The philosophy of Emil Fackenheim: from revelation to the Holocaust - Green, Kenneth Hart (Cambridge University Press, 2020)
"Fackenheim launched his career as a theologian by confronting the modern crisis of faith, which he regarded as the most urgent matter both for philosophy attuned to religion, and for committed religious thought. He believed that this is a crisis not only for Judaism, but for all modern religious thought, because modern philosophy has done as much as possible to make even the most basic religious faith questionable, if not untenable, to modern man, for it assaults the basic belief that God makes himself manifest through "personal" converse with human beings"